Peptídeos antimicrobianos da formiga gigante Dinoponera quadriceps: ação sobre microrganismos com perfil crítico de resistência a antibióticos e antifúngicos - Lima, Hilania Valéria Dodou (2021)
Microbial resistance has been a growing global public health problem. The increase in the number of antimicrobial-resistant strains and the constant alerts of international agencies have stimulated and directed research to discover and develop new molecules with promising antimicrobial potential. Antimicrobial peptides (AMPs) have been considered innovative antimicrobial agents. They are seen as advantageous for the development of drugs because, in general, they have a broad spectrum of activity, with complex mechanisms of action, which would hinder the emergence of antibiotic resistance. The venom of the giant ant Dinoponera quadriceps constitutes a mixture of bioactive organic compounds, including AMPs, which deserve meticulous investigation for their pharmacological potential. This study aimed to evaluate the antimicrobial potential of synthetic peptides derived from the venom of the giant ant D. quadriceps. The present study culminates with the publication of three scientific articles. In the first article, the components of low molecular weight and peptides of the giant ant D. quadriceps venom and its antimicrobial, hemolytic, and histamine-releasing properties were analyzed. In the second publication, the action of synthetic peptides on different Candida species was evaluated, in addition to its potential to synergistically modulate the action of commercially available antifungal drugs and their cytotoxic potential on red cells. In the third publication, the action of AMPs on resistant bacteria species, considered a critical priority by the WHO and their ability to synergistically modulate conventional antibiotics action and their hemolytic potential, was evaluated. The analysis of the venom constituents of D. quadriceps showed low molecular weight components, such as biogenic amines, free amino acids, and bioactive peptides, with sequences ranging from 4 to 28 amino acid residues. Five known classes of antimicrobial peptides (AMPs) were found, such as dermaseptin-, defensin-, pilosulin-, ponericin- and temporin-like types. In preliminary trials, two classes of these synthetic AMPs, dinoponeratoxins Dq-2562 (a pilosulin-like) and Dq-3162 (a ponericin-like) were antimicrobial hemolytic and histamine-releasing action. Dq‐2562 and Dq‐1503 (pilosulin-like) and Dq‐3162 (ponericin-like) were the most active in antifungal peptides, exhibiting a broad spectrum of antifungal activity in vitro, with MICs in the range of 0.625 to 10 μM. The combination of peptides and conventional antimycotic drugs showed a synergistic reduction in the MIC values of both substances. The fungicide and fungistatic activity of individual peptides and peptides combined with antimycotics were time-dependent, with a rapid onset of action and long-lasting effect.Synthetic peptide Dq-3162 demonstrated antibacterial efficacy, with MICs between 5 and 10 μM, with rapid-onset and prolonged duration bacteriostatic and bactericidal effects, enhancing the action of the drugs meropenem, imipenem, and gentamicin against Gram-negative bacteria resistant to carbapenems, which are a critical priority by the WHO. In summary, synthetic dinoponeratoxins are promising antifungal and antibacterial peptides useful for developing combined alternatives against multi-drug resistant microorganisms.